Synthesis of levulinic acid from oil palm mesocarp fiber by acid hydrolysis - Zulkipli, Nor Akhlisah (2019)
Levulinic acid (LA) can be produced from both C6 and C5 carbohydrates via dehydration and hydrolysis processes of biomass. This study focuses on the production of LA from oil palm mesocarp fiber (OPMF). From proximate and thermogravimetric analysis (TGA), it was found that OPMF has 21.16 - 29.73% of cellulose, hemicellulose 21.81 – 27.61%, lignin 10.39 – 30.80%, ash 6.39% and extractive 25.23%. It is difficult to produce high yield of LA from the biomass due to generation of humins during hydrolysis reaction. Moreover, the high content of silica bodies on OPMF surface also causes lower sugar production which affects the formation of LA. Thus, pretreatment is needed to improve the yield of LA. This study aimed to investigate the effect of several pretreatments on the synthesis of LA. Four pretreatments were conducted; acid pretreatment, ultrasonic-assisted acid pretreatment, alkali pretreatment and ultrasonicassisted alkali pretreatment. Sulfuric acid (H2SO4) and sodium hydroxide (NaOH) were used as catalysts in pretreatment. For acid and alkaline pretreatments, samples were pretreated with different temperatures (60 °C, 80 °C and 100 °C). The parameter for ultrasonic-assisted pretreatment was sonication power (40%, 60% and 80%). The highest content of HMF produced after pretreatment from all pretreatments was 1.71% pretreated by 6% (v/v) sulphuric acid pretreatment without ultrasonic at 100 ⁰C. Direct hydrolysis of biomass was proposed after it was discovered that most of the sugars after pretreatment were present in the liquor. The maximum yield of LA was 20.54% obtained from direct acid hydrolysis of sample which was pretreated at 100 ⁰C using 6% (v/v) H2SO4 solution. The results on morphological structure of treated OPMF fiber after SEM analysis showed the evidence of silica bodies removal from the surface of OPMF fiber thus allowed for a direct exposure of acid pretreatment and acid hydrolysis. FTIR analysis suggested that the formation of carbonyl groups indicates the formation of LA in hydrolysis samples. TGA results indicated that the sample which produced highest amount of levulinic acid had lowest activation energy in the reaction. The second objective is to the study effect of process conditions on the hydrolysis of OPMF into LA using Response Surface Methodology (RSM). The pretreatment method chosen in this step was based on the results obtained from the first objective. The pretreated samples were hydrolyzed in acid hydrolysis reactor. Three parameters were investigated; reaction time (2 – 4 hours), acid concentration (1 - 3% (v/v) H2SO4) and temperature of reaction (120 – 160 °C). The highest content of LA 17.88% was produced at the temperature 160 ⁰C, using 3% sulphuric acid concentration for 4 hours. Since these are the highest conditions for each parameter, the optimized condition could not be determined due to the limitation of reactor specification for acid hydrolysis reaction.